SOSIALISASI REPITALISASI USAHA KESEHATAN SEKOLAH DI SMP YAPIM DELI TUA - Rizka Annisa; Fithri Handayani Lubis; Sulastri Br Ginting (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
School Health Efforts (UKS) are also health education efforts that are carried out in an integrated, conscious, planned, directed and responsible manner in instilling, growing, developing, and guiding to live, enjoy and implement the principles of healthy living in the daily lives of students. With the enactment of Law Number 32 of 2004, the various UKS implementation programs in each region are basically left entirely to the UKS Guidance Team in their respective regions to determine program priorities. Based on the observations of the central UKS Guidance Team, it turns out that the implementation of UKS so far is still not as expected. Therefore, it is deemed necessary to empower the UKS structure at every level in order to strengthen the implementation of UKS programs. As we know, UKS is a vehicle to improve the ability to live a healthy life and the health status of students as early as possible. With the program from the government about the UKS strata level. One of UKS activities is health services for school residents. With the existence of health services at SMP Yapim Deli Tua, UKS equipment in elementary schools must be adequate and meet the standards set by the government. As well as the UKS facilities and infrastructure must be considered by every school. With the School Operational Assistance (BOS) fund, schools should be able to allocate funds to complete UKS facilities and infrastructure, but sometimes problems related to UKS facilities and infrastructure are often ignored by the school. In addition to funding problems that affect the fulfillment of UKS facilities and infrastructure needs, there is also limited knowledge of teachers about the strata level in UKS. This will also affect the fulfillment of UKS infrastructure facilities. In addition to the knowledge that teachers lack, socialization about strata in UKS by related parties is also lacking. Therefore, there are many factors that cause the lack of facilities and infrastructure at SMP Yapim Deli Tua. The hope is that schools in fulfilling UKS facilities and infrastructure can be fulfilled in their entirety. The reality in schools is that many schools do not meet the adequate UKS infrastructure and in accordance with the recommendations of the government.